Exploring the reasons and significant influencing factors of serious turnover intentions among nurses in Saudi Arabia - Zyad T. Saleh; Aziz Aslanoğlu; Rami A. Elshatarat; Majed S. Al-Za’areer; Wesam T. Almagharbeh; Asim A. Alhejaili; Bandar Naffaa Alhumaidi; Hekmat Y. Al-Akash; Muwafaq M. Al-Momani; Hazem A. Alfanash; Amal Ali Alasmari (Journal of Education and Health Promotion)
BACKGROUND: Nursing turnover is a significant concern in healthcare systems. This study aimed to explore the influencing factors of nurses’ turnover in Saudi Arabia. MATERIALS AND METHODS: This cross-sectional study was conducted between August 2023 and December 2023 at various hospitals in Saudi Arabia. A total of 397 nurses were enrolled using the convenience sampling method. Data on turnover intentions were collected through a structured questionnaire designed to capture various factors influencing nurses’ decisions to leave their current positions. The questionnaire included items on demographics, work environment, job satisfaction, and potential reasons for turnover. Statistical analyses in SPSS included descriptive statistics, Chi-square tests, and multiple logistic regression to identify and predict factors influencing serious turnover intentions. RESULTS: A significant proportion expressed their intention to leave their current hospital with 38.6% contemplated leaving. Notably, 53.7% intended to turnover, with 18.4% seriously considering it. Non-Saudi nurses were more inclined to cite excessive workload and poor management. Predictors of serious turnover intentions included non-Saudi nationality, lower salary, shorter experience as a registered nurse, and working in critical care. Dissatisfaction with salary, organizational communication, and lack of recognition also contributed. CONCLUSION: The study emphasizes the need for targeted interventions to address factors driving nurse turnover in Saudi Arabia. Health policymakers and managers should improve salary structures and managerial support to reduce turnover intentions. Implementing these measures will not only improve job satisfaction among nurses but also ensure a more stable and effective healthcare workforce, ultimately leading to better patient care and outcomes.